Effect of grinding time in bead mill and size of working bodies on the particle size of suspension - Yaremchuk, Pavlo; Ponomarenko, Artem; Hrininh-Hera, Kateryna; Gavva, Oleksandr (My University, 2024)
Knowledge of the change in particle size during grinding in a bead mill is necessary for proper planning and optimization of the production process. Bead size of 1.5 mm is more energy-efficient and significantly more effective in terms of productivity (grinding time). The particle size changes insignificantly after 10–15 minutes, and grinding should be stopped.
Keywords: bead mill; бісерний млин; подрібнення надтонке; ultrafine grinding; кафедра мехатроніки та пакувальної техніки; кафедра машин і апаратів харчових та фармацевтичних виробництв